2013
DOI: 10.1016/j.system.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of socio-economic factors in motivation to learn English as a foreign language: The case of Chile

Abstract: In the present study we surveyed the English language learning motivations of 740 secondary school students belonging to different social classes in the capital of Chile, Santiago. We applied multiple analyses of variance to analyze how motivational variables differ depending on students' social class. The results suggest that social class has an overall medium-size effect on motivational factors with self-efficacy beliefs being the most strongly related to socioeconomic status. The most important differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 41 publications
5
80
3
4
Order By: Relevance
“…With regard to motivation, both Lifrieri (2005) and Kormos and Kiddle (2013) found that learners from different social classes have different motivational profiles, with upper middle-class learners showing a significant advantage, particularly with regard to the 'self-efficacy' dimension. In particular, Lifrieri (2005) studied the relationship between SES and motivation in 39 fourth-grade students (9-10 years old) enrolled in six public schools located on the outskirts of Buenos Aires, Argentina.…”
Section: Motivationmentioning
confidence: 99%
“…With regard to motivation, both Lifrieri (2005) and Kormos and Kiddle (2013) found that learners from different social classes have different motivational profiles, with upper middle-class learners showing a significant advantage, particularly with regard to the 'self-efficacy' dimension. In particular, Lifrieri (2005) studied the relationship between SES and motivation in 39 fourth-grade students (9-10 years old) enrolled in six public schools located on the outskirts of Buenos Aires, Argentina.…”
Section: Motivationmentioning
confidence: 99%
“…Understanding the role of learners' goals, self-related beliefs and self-regulatory processes is essential before effective instructional programs for learners studying in different social contexts can be designed and implemented (Kormos & Kiddle, 2013). Socioeconomic status, however, does not only affect language learning outcomes but also has an influence on motivation to learn, self-regulation, and students' self-related beliefs (Fan, 2011).…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…The children cannot discuss their learning problems in school with their parents at home because most parents of disadvantaged children are not well educated. Additionally, Kormos, J and Kiddle, T (2013) The third factor that influences their cognitive performance is that instead of providing nutritious food that can support their cognitive development, their parents are forced to provide less nutritious food in order to make ends meet. Understandable, good quality school takes price.…”
Section: Family Financial Problems Affect Students' Cognitive Performmentioning
confidence: 99%
“…This opinion influences their behavior toward the language (Kormos, J and Kiddle, T ;. It makes their awareness to learn English is decreased and lowering their motivation to learn.…”
Section: Disadvantaged Students Commonly Have Instrumental Motivationmentioning
confidence: 99%